Breeding Biology of Little Egret Egretta garzetta in Kerala, Southern India - Seedikkoya, K.; Azeez, P. A. (Journal of the Bombay Natural History Society (JBNHS), 2012)
The breeding biology of Little Egret Egretta garzetta was studied during 1999-2002 in Kerala, southern India. Investigations were made early in the monsoon to locate nesting colonies, and some of these selected for further study. Characteristics of the nest and eggs, incubation, and the data on hatching were recorded. In building the nests, the birds used materials ranging from 19.18 to 36.64 cm in length, from 35 plant species. Clutch size varied from 2 to 6,4 being the most common. Hatching success was about 74%. As in adult birds, the food of the nestlings was mainly fish. Both the parents took part in feeding the young.